Pelvic Lymph Node Dissection in Penile Cancer With Inguinal Lymph Node Extranodal Extension: A Multicenter Experience - Li, Zai-Shang; Han, Hui; Deng, Chuang-Zhong; Li, Yong-Hong; Wu, Chong; Chen, Peng; Liu, Zhuo-Wei; Qin, Zi-Ke; Zhou, Fang-Jian (Frontiers in Surgery, 2021)
Background: The aim of this study is to determine the necessary extent of penile lymph node dissection (PLND) in penile cancer patients with inguinal lymph node extracapsular extension (ILN-ENE). Methods: Penile cancer patients who underwent PLND in 15 centers from January 2006 to April 2020 were retrospectively analyzed. PLND was performed in patients with ILN-ENE. Results: Sixty-two patients with ILN-ENE were included in the analysis. A total of 51.6% (32/62) of the patients were confirmed to have pelvic lymph node metastasis (PLNM), and 31.3% (10/32) of patients were confirmed to have multiple PLNMs. Of the patients with metastases, 59.4% (19/32) had bilateral inguinal lymph node metastasis (ILNM). According to the anatomical structure, 71.9% (23/32) of the patients had PLNM in the external iliac region, and 56.2% (18/32) had PLNM in the obturator region. Among those with oligo-PLNM, 65.1% (28/43) of the patients had PLNM in the external iliac region and 38.9% (15/43) had PLNM in the obturator region. A significant overall survival difference was observed between patients with the bilateral ILNM and unilateral ILNM (36-month: 21.2 vs. 53.7%, respectively, P = 0.023). Patients with bilateral ILNM had relatively poor metastasis-free survival compared with unilateral ILNM (36-month: 33.0 vs. 13.9%, respectively, P = 0.051). Conclusions: The external iliac and obturator region were the most commonly affected regions in patients with ILN-ENE, and these regions were the only affected regions in patients with oligo-PLNM. Patients with bilateral ILNM had a high risk of PLNM and worse survival.